Gendering jobs : corporate strategy, managerial control and the dynamics of job segregation - Morgan, Glenn [Verfasser]; Knights, David [Verfasser] (My University, 1991)
"The paper argues that the understanding of gender relations at work neccessitates an explicit consideration of corporate strategy and managerial practices. Through the detailed examination of relations within a financial services company, the authors show how certain important issues of corporate strategy revolve around the gendered nature of particular jobs. The struggle within senior management to develop a corporate strategy was reflected in the lower levels of the organization in a struggle between particular groups over the maintenance of gendered identities and the control of particular work settings. The struggle between different groups of men, as well as between men and women, was conducted in terms of who was best able to contribute to the success of the company's corporate strategy. The paper argues that an important dimension of the gendered order in work settings is to be located in the dynamics of corporate strategy formation and development in organizations. Analyses of gender at work, it is argued, need to take into account some of the issues of management control and corporate strategy." (author's abstract) ((en)) In dem Papier wird die Ansicht vertreten, dass die Geschlechterverhältnisse am Arbeitsplatz vor dem Hintergrund des jeweiligen Unternehmensziels und entsprechender Managementpraktiken analysiert werden müssen. Hierzu wurden im Rahmen einer Fallstudie die verschiedenen Entscheidungsebenen eines britischen Unternehmens für Versicherungsdienstleistungen untersucht. Insbesondere wird herausgearbeitet, welche geschlechtsspezifischen Identitäten und Kulturen sich in bestimmten Tätigkeitsbereichen gebildet haben, bzw. in Hinblick auf das Unternehmensziel gefördert wurden (z.B. Macho-Typ im Verkauf, patriarchalischer Typ im Management). (IAB)
Geschlechterverhältnisse am Arbeitsplatz. Unternehmensstrategie, Management-Kontrolle und die Dynamik der Segregation
Keywords: L 6 Qualität; G 1.2 Arbeitsmarkt; G 1.2.4.2.4 Kredit und Versicherung; S 6.4.1.2 Dienstleistungskaufleute; G 2.3.1 Arbeitsteilung & -organisation; G 2.4.4 Biografiegestaltung; G 1.3.3.1 Qualifikationsverwertung; I 2.2.1 Westeuropa; Unternehmensziel; Arbeitsmarktsegmentation; Geschlechtsspezifische Faktoren; Interner Arbeitsmarkt; Versicherungsgewerbe; Versicherungskaufmann; Arbeitsanforderungen; Berufsproblem; Berufliche Identität; Großbritannien